Features and Possible Causes of the Extreme Precipitation Anomaly in China During Winter 2019/2020 - Xiang, Li; Chenqi, Wang; Ling, Tiejun; Sun, Cheng; Zhang, Yunfei; Wang, Jian (Frontiers in Earth Science, 2020)
In this paper, the features and possible causes of extreme precipitation in the winter of 2019/2020 in China are investigated based on the observational station daily dataset provided by the China Meteorological Administration and the ECMWF ERA5 reanalysis dataset. Record-breaking precipitations are found in most areas of China in the winter of 2019/2020, particularly for the north of China. The magnitude of precipitation in south (north) of China in 2019/2020 increase 0.39mm/day (0.15mm/day), about 39.0% (105.5%) compared with the climatological mean. Moisture budget analysis shows that contributions of atmospheric circulation anomaly on horizontal moisture advection and total moisture flux convergence are primarily responsible for the positive anomalies of precipitation in China. Further analysis suggests that the weakened East Asian Trough and the anti-cyclone circulation anomaly over the Sea of Japan favor the transportation of low-level warm and humid airflow from the Northwest Pacific and the East China Sea to the north of China. Meanwhile, the westward movement of the Subtropical High and the Southern Branch Trough anomalies transport low-level warm and humid air from the Bay of Bengal and the South China Sea to south of China. The warm moist air flows northeastward from the East China Sea, Bay of Bengal and the South China Sea while the climatological cold wind flows southeastward, which causes the increase of local precipitation in the winter of 2019/2020. In consideration of the fact that stratospheric polar vortex anomaly has a process of downward propagation to the troposphere, it is of great significance to study the changes of the stratosphere and the relationships between stratosphere and troposphere.